R.Owen’s private initiative on people education and elementary education in Great Britain of the 19th century - Мокроменко, О. В. (Scientific notes of the pedagogical department, 2018)
The article studies the issue of the theory and practice of the elementary education development in Great Britain of the 19th century. A correlation between private initiative and State assistance in the formation process of the elementary schools net has been defined and proved by the samples from the history of the elementary education development. Special attention is given to the investigation of R.Owen’s private initiative on people education activity. Three periods in this activity have been identified according to changing R.Owen’s philosophy, publishing new works, searching for new forms of his private initiative on people education activity. New Lenark’s period in his education activity has been considered. The main trends of R.Owen’s education activity in the denoted period have been characterized. The goal of R.Owen’s public and education activity has been determined as paying attention of people and British government to the issue of creating and activity of elementary education schools. Assistance for two British educational specialists has been defined as one of the main trends in R.Owen’s education activity. Taking a part in the creating standards base of the elementary education development including Factory Acts (1802-1819) has been described as a considerable contribution in R.Owen’s education activity. R.Owen as a founder of kindergarten in Great Britain in 1816 ( a part of his Institute) has been ascertained in the investigation. R.Owen’s studying both native and foreign educational specialists experience has been pronounced the significant part of his education activity. It is concluded that elementary education school activity in Great Britain of the 19th century is characterized by private initiative. R.Owen’s education activity has received recognition in the elementary education development in Great Britain of the 19th century.